EFFECT OF ANTIOXIDANT AND TOTAL PHENOLS VALUES OF LABMANUFACTURED BISCUITS BY REPLACING WHEAT FLOUR WITH DIFFERENT PROPORTIONS OF TANGERINE PEEL POWDER - Ahmad Muhsin Al-janabi; Roaa Waleed Farooq (European Journal of Agricultural and Rural Education, 2024)
Study focused on impact of incorporating three different types of tangerine husk powder in to wheat flour. The inclusion percentages ranged from 12,8,4%. Antioxidants were estimated as they recorded an increase in the value of antioxidants, as it was noted that this value increased by increasing the replacement rates, as it reached at a concentration of A3 about 9.01 compared to the control sample (A), which amounted to 4.37, while in the raw materials for each of Fit reached 13.6 and F11.30 . The percentage of total phenols for manufactured biscuits and raw materials was also estimated, as there were significant differences between the ratios , as high percentage is recorded for A3 treatment, which amounted to 3.7%, and low percentage at A treatment amounted to 1.5%, while the A1 & A2 treatment was 1.59 and 2.7% respectively. While the ratio of total phenols to raw materials for coefficients F1and F is recorded (4.09&1.8)% respectively